2020
DOI: 10.1111/scd.12463
|View full text |Cite
|
Sign up to set email alerts
|

I have been refused to be treated by three dentists”: Barriers to patient care

Abstract: Background:Factor X deficiency (known as; Stuart-Prower factor deficiency or F10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, there are a very few publications related to access to dental care for these patients. 1,3,9,19 Public policy makers and health service providers must prioritize oral health to improve general health and quality of life of people with these conditions. Therefore, the aim of this study was to identify the main barriers to access dental care for this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a very few publications related to access to dental care for these patients. 1,3,9,19 Public policy makers and health service providers must prioritize oral health to improve general health and quality of life of people with these conditions. Therefore, the aim of this study was to identify the main barriers to access dental care for this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, in the same qualitative case report, the patient himself reported that he tried sometimes to avoid brushing his teeth to prevent sudden, uncontrolled gingival bleeding. 7 Fear from I G U R E 2 Participants' perceived barriers based on the accessibility model as defined by Penchansky and Thomas 19 uncontrolled gingival bleeding could increase people with CBDs anxiety level, hence it reduces their perceived confidence level toward their dentists' knowledge and skills, as shown in this study's results. Thereby, it seems that fear from uncontrolled gingival bleeding worsens the scenario and adds a further explanation about why people with CBDs might be refused to be treated by dentists, as this impacts negatively on patient-dentists relationship.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, adult participants reported their fear from uncontrolled gingival is also the reason behind why they could not brush their teeth sometimes . A qualitative case report showed that a male patient (31 years old) with CBD (factor X deficiency) refused to be treated by three dentists who were worried about oral bleeding 7 . Additionally, in the same qualitative case report, the patient himself reported that he tried sometimes to avoid brushing his teeth to prevent sudden, uncontrolled gingival bleeding 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations